Book Reviews (Journal of Finance, 1995)
Book reviewed in this article: Contemporary Financial Intermediation . By STUART I. GREENBAUM and ANJAN V. THAKOR. Reminiscences of a Stock Operator . By EDWIN LEFÈVRE. New York: John Wiley&Sons Cases in Financial Engineering: Applied Studies of Financial Innovation . By SCOTT P. MASON, ROBERT C. MERTON, ANDRE F. PEROLD, and PETER TUFANO. Lease or Buy . By JAMES S. SCHALLHEIM. Boston